ANALISIS PENGUKURAN KINERJA REKSA DANA DENGAN METODE SHARPE DAN METODE TREYNOR (Studi Pada Reksa Dana Saham Periode Tahun 2011-2012) - Barus, Gratia Atanka; Kholiq Mahfud, Mohammad (Faculty of Economics and Business Diponegoro University, 2013)
In this globalization era, a lot of investors who do not have much time in managing theirfunds and limited expertise to calculate the risks of their investments are doing. Now is not the major problem that prevents investors to invest for potential investors can give confidence to the investment managers to manage their funds. This study aimed to determine whether the performance of equity funds have performed better than the market as a comparator (IHSG) by using Sharpe and Treynor and to see is there a difference in ratings between Sharpe methods and Treynor methods.There were 10 mutual funds which are used as a sample study. The sampling method used was purposive sampling. This study uses Sharpe and Treynor methods. The type of data used is secondary data is data that NAB is a sample of March 2011 to March 2012 in the form of daily data. Mutual funds are said to have good performance when the greater value of Sharpe and Treynor ratio, the better the performance of mutual fund.The results of the analysis using the Sharpe suggests that there are 5 (five) Mutual Funds that have a good performance and are 5 (five) Mutual Funds have performed below IHSG performance analysis using Treynor shows that there are 9 Mutual Funds that have performed well. There are 5 (five) Equity Funds have not changed either using the method of Sharpe and Treynor and 5 (five) Equity Fund those rating changed either using the Sharpe and Treynor methods